Got Talent: Peyssonnelia globally showcases its skills - Gabriel, Daniela (2019)
ABSTRACT: The crust forming genus Peyssonnelia Decaisne is a taxon of great ecological importance, with some species involved in the establishment of rhodoliths. Comparative morphological and molecular analyses demonstrate a greater diversity of peyssonnelioid species than was previously reported. In chloroplast-encoded rbcL-based trees, species referred to as Peyssonnelia in the literature do not group together, but are scattered among other genera that were not currently placed in the Peyssonneliaceae. Two recently reported genera for the Gulf of Mexico, “ Polystrata” and Metapeyssonnelia, were excluded from the family, and together with a third clade are nested inside the Rhizophyllidaceae of the Dumontiaceae-complex. The Rhizophyllidaceae is newly reported for the Gulf of Mexico, with six species. The number of distinct species of Peyssonneliaceae now present in the Gulf of Mexico has increased from 6 to 21. On the other hand, the number of Peyssonnelia reported for the Azores was reduced from five to one species. Some species placed in Cruoriella and Cruoriopsis actually belong in the Peyssonneliaceae. New combinations are being proposed to accommodate known and new species in Cruoriella, and in two formerly monotypic genera, Sonderophycus and Riquetophycus. The Peyssonneliaceae forms a monophyletic assemblage that could not be maintained in the Gigartinales and thus a new order was constituted, Peyssonneliales, unrelated to the cluster of families centred around the Halymeniaceae of the Halymeniales, or the Gigartinaceae of the Gigartinales.